Examination of Leadership Style with MLQ Among Small Enterprices in Szabolcs-Szatmár Bereg County - Filep, Roland; Filep, Roland (International Journal of Engineering and Management Sciences, 2018)
The Full Range of Leadership Model describes different behaviors and styles that differentiate leaders. Managers and leaders use each style, but not egally. The Multifactor Leadership Questionnaire (MLQ) measures the full spectrum of leadership styles. It is widely used by researchers and practitioners. In my paper, after a short theoretical review of the topic and the description of the styles, my empirical analysis is also presented. In my work I examined the leadership style of chief executives of small enterprises in Szabolcs-Szatmár-Bereg county, with MLQ.